Incidence of pre-, peri-, and post-natal birth and developmental problems of children with sensory processing disorder and children with autism spectrum disorder - May-Benson, Teresa A.; Koomar, Jane; Teasdale, Alison (Frontiers in Integrative Neuroscience, 2009)
As the diagnosis of sensory processing disorder (SPD) is advanced, it is important to investigate potential contributing factors to this disorder as well as early diagnostic signs. An exploratory descriptive study, utilizing retrospective chart review, was conducted to investigate the incidence of pre-, peri- and post-natal, birth and developmental problems in a sample of 1000 children with SPD and of 467 children with autism spectrum disorder (ASD), who also had SPD. This study revealed that although no one factor was strongly associated with SPD or ASD, an average of seven events for children with SPD and eight events for children with ASD occurred across categories. These included: one pre-natal/pregnancy problem, delivery complication, assisted delivery, gestational or birth-related injury/illness; one or more early childhood illnesses or injuries; two or more infancy/early childhood developmental problems; and one or more delayed early childhood developmental milestones. When comparing results to national studies of the typical population, most remarkable was the incidence of jaundice, three to four times higher in both the SPD and ASD groups than in typical children. In addition, rates of breech position, cord wrap/ prolapse, assisted delivery methods (particularly forceps and suction deliveries), and high birth-weight were greater in both groups. Incidence of premature birth was higher in the ASD although not significantly different from the SPD group. Also of note was a high frequency of absent or brief crawling phase, and high percentages of problems with ear infections, allergies, and maternal stresses during pregnancy.